2020
DOI: 10.1101/2020.06.04.132811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Central processing of leg proprioception inDrosophila

Abstract: Proprioception, the sense of self-movement and position, is mediated by mechanosensory neurons that detect diverse features of body kinematics. Although proprioceptive feedback is crucial for accurate motor control, little is known about how downstream circuits transform limb sensory information to guide motor output. Here, we investigate neural circuits in Drosophila that process proprioceptive information from the fly leg. We identify three cell-types from distinct developmental lineages that are positioned … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 93 publications
(89 reference statements)
4
21
1
Order By: Relevance
“…However, blocking acetylcholine receptors with MLA reduced but did not eliminate club-driven calcium signals in 10Bα neurons (Figure 3C-D). These data suggest that the connection between club and 10Bα neurons consists of mixed chemical/electrical signaling, which is consistent with previous work (Agrawal et al, 2020). Interestingly, we observed that the time to peak of the 10Bα calcium signals was significantly longer in the presence of MLA (Figure 3D), which suggests that chemical and electrical transmission may have distinct temporal dynamics.…”
Section: Bα a Vnc Cell Class Downstream Of The Club Integrates Bidirectional Movements And Vibration Signaling From Different Legs Acrosssupporting
confidence: 92%
See 2 more Smart Citations
“…However, blocking acetylcholine receptors with MLA reduced but did not eliminate club-driven calcium signals in 10Bα neurons (Figure 3C-D). These data suggest that the connection between club and 10Bα neurons consists of mixed chemical/electrical signaling, which is consistent with previous work (Agrawal et al, 2020). Interestingly, we observed that the time to peak of the 10Bα calcium signals was significantly longer in the presence of MLA (Figure 3D), which suggests that chemical and electrical transmission may have distinct temporal dynamics.…”
Section: Bα a Vnc Cell Class Downstream Of The Club Integrates Bidirectional Movements And Vibration Signaling From Different Legs Acrosssupporting
confidence: 92%
“…A subset of 10Bα neurons also project to the brain, arborizing in the contralateral antennal mechanosensory and motor center (AMMC, data not shown). Previous work showed that optogenetic activation of 10Bα neurons caused walking flies to pause, consistent with a role in detecting substrate vibration (Agrawal et al, 2020).…”
Section: Bα a Vnc Cell Class Downstream Of The Club Integrates Bidirectional Movements And Vibration Signaling From Different Legs Acrosssupporting
confidence: 58%
See 1 more Smart Citation
“…Second, these mechanosensory neurons are morphologically diverse and have topographically organized projections into the CNS ( Kamikouchi et al, 2006 ; Mamiya et al, 2018 ). Third, the subpopulations can differentially interface with downstream circuitry to influence distinct behaviors or movements ( Agrawal et al, 2020 ; Hampel et al, 2015 ; Kim et al, 2020 ; Vaughan et al, 2014 ). Fourth, similar features of mechanosensory stimuli can be represented in neurons downstream of the JO and FeCO ( Agrawal et al, 2020 ; Chang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the subpopulations can differentially interface with downstream circuitry to influence distinct behaviors or movements ( Agrawal et al, 2020 ; Hampel et al, 2015 ; Kim et al, 2020 ; Vaughan et al, 2014 ). Fourth, similar features of mechanosensory stimuli can be represented in neurons downstream of the JO and FeCO ( Agrawal et al, 2020 ; Chang et al, 2016 ). These commonalities suggest that results obtained through studies of different chordotonal organs could be mutually informative.…”
Section: Discussionmentioning
confidence: 99%